(untitled) (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Background: Inhibited colostrum flow in postpartum moms can result from a variety of causes, such as insufficient prolactin and oxytocin hormone stimulation. To increase prolactin and oxytocin levels, lactation and oxytocin massages in conjunction with lavender aromatherapy can hasten the flow of colostrum. The mother may feel relaxed and at ease after either of these interventions. Research Purpose: This study aimed to determine the differences between lactation and oxytocin massage combined with lavender aromatherapy on colostrum release in normal postpartum mothers at Kartika Jaya Clinic. Method: This study used a Quasi Experiment design with a two-group posttest-only design. The sample comprised 32 postpartum mothers and was collected using an accidental sampling technique—measurement of variables using colostrum discharge observation sheets. Data were processed using the Mann-Whitney test. Research Results: From 16 postpartum mothers in each group, the mean or average value of colostrum discharge time in the lactation massage intervention was 10.75 hours and in the oxytocin massage intervention was 22.25 hours, where in the provision of oxytocin massage intervention, 11.5 hours longer colostrum discharge time compared to lactation massage intervention. And the Asymp value. Sig. (2-tailed) = 0.001 was obtained. Because the Asymp value. Sig. (2-tailed) 0.001 <0.005, then H₀ was rejected, and Ha was accepted, so there was a difference in lactation massage and oxytocin massage combined with lavender aromatherapy at the time of colostrum discharge in normal postpartum mothers at Kartika Jaya Clinic. Conclusion: This indicates a difference between lactation and oxytocin massage combined with lavender aromatherapy on colostrum production in normal postpartum mothers at Kartika Jaya Clinic. Suggestion: Postpartum mothers can apply lactation massage because it is effective in helping breast milk production. Medical personnel, especially midwives, should be more skilled and, if necessary, certified in lactation massage.